Two-decade variability and trend of chlorophyll-a in the Arabian Sea and Persian Gulf based on reconstructed satellite data - Yang, Mengmeng; Khan, Faisal Ahmed; Fang, Hua; Maúre, Elígio de Raús; Ishizaka, Joji; Liu, Dong; Wang, Shengqiang (Frontiers in Marine Science, 2024)
The spatiotemporal variability of chlorophyll-a (Chl-a) in the Arabian Sea (AS) and Persian Gulf (PG) has been the subject of extensive research. However, comprehensive analyses are often hindered by data gaps and limited study periods, with long-term trends remaining less understood. This study aims to investigate the spatiotemporal variability and long-term trends of Chl-a from 2001 to 2019 based on reconstructed satellite data, and also examine the influence of sea surface temperature (SST) and wind patterns. To achieve this, we reconstructed MODIS-Terra monthly Chl-a and SST datasets using the Data Interpolating Empirical Orthogonal Functions (DINEOF) method, demonstrating high accuracy through cross-validation. The results show pronounced seasonal variability, with Chl-a peaks exceeding 3 mg m⁻³ during southwestern monsoons and ranging between 1-3 mg m⁻³ during northeastern monsoons, while the lowest Chl-a occurred in pre-and post-southwestern monsoons (transitional months). The highest Chl-a levels were found in the western and northeastern AS. These were driven primarily by the southwestern (SW) monsoon in summer and the northeastern (NE) monsoon in winter. Trend analysis using the Sen's slope and Mann-Kendall test revealed a significant decrease in Chl-a anomalies (Chl-a_A) (-0.002 to 0) along the ASPG coasts, with small areas of increase (~0.005) in the southeastern AS and southern PG. Correlation analysis showed that rising SST_A reduced Chl-a_A in the western AS, 36 while increased Wind_A boosted Chl-a_A in the western AS and reduced it in the southern PG. 37 This research advances our understanding of the complex dynamics influencing ASPG ecosystems. 38 39 KEYWORDS 40 Chlorophyll-a, Data Interpolating Empirical Orthogonal Function, Arabian Sea and Persian Gulf, 41 MODIS, sea surface temperature, wind. 42 43